2022
DOI: 10.3390/polym14071349
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of Piperine Nanoparticles: In Vitro Breast Cancer Cell Line and In Vivo Evaluation

Abstract: Piperine (PPN), one of the most investigated phytochemicals, is known to have excellent therapeutic efficacy against a variety of ailments including breast cancer. However, its physicochemical properties such as poor aqueous solubility restrict its clinical application. Therefore, the present investigation was designed to develop PPN encapsulated lipid polymer hybrid nanoparticles (PPN-LPHNPs) to overcome the limitation. The developed PPN-LPHNPs were optimized by the three-factor, three-level Box–Behnken desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…In addition, the greater cytotoxicity was attributed to small size, spherical morphology, and cytosolic PPN delivery from the nanocarrier. , Our finding also corroborated a previously published report. Kazmi et al studied the anticancer effect of PPN-loaded polymeric nanoparticles on MCF-7 cells . The researcher reported that the developed NPs showed IC 50 values of 21.32 ± 2.17 and 9.46 ± 2.18 μg/mL at 48 and 72 h, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, the greater cytotoxicity was attributed to small size, spherical morphology, and cytosolic PPN delivery from the nanocarrier. , Our finding also corroborated a previously published report. Kazmi et al studied the anticancer effect of PPN-loaded polymeric nanoparticles on MCF-7 cells . The researcher reported that the developed NPs showed IC 50 values of 21.32 ± 2.17 and 9.46 ± 2.18 μg/mL at 48 and 72 h, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Kazmi et al studied the anticancer effect of PPN-loaded polymeric nanoparticles on MCF-7 cells. 21 The researcher reported that the developed NPs showed IC 50 values of 21.32 ± 2.17 and 9.46 ± 2.18 μg/mL at 48 and 72 h, respectively. Therefore, it can be inferred that the development of PPN-encapsulated PCL-NPs can enhance the therapeutic efficacy against BC.…”
Section: Stability Studymentioning
confidence: 99%
See 2 more Smart Citations
“…After centrifuging the dispersion for 12 min at 10,000 rpm, the foreign polymeric substances was separated from the supernatant. The clear supernantant solution was examined by HPLC at 415 nm and 342 nm, respectively, to ascertain the amount of loaded mangiferin and piperine in the developed FAP nanoparticle system [18][19][20].…”
Section: Characterization Parameters Of Fap Nanoparticles and Plga Na...mentioning
confidence: 99%